2017
DOI: 10.18632/oncotarget.14982
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-treated cancer cells modulate macrophage polarization through AMPK-NF-κB signaling

Abstract: Accumulating evidence is indicating metformin to possess the potential ability in preventing tumor development and suppressing cancer growth. However, the exact mechanism of its antitumorigenic effects is still not clear. We found that metformin suppressed the ability of cancer to skew macrophage toward M2 phenotype. Metformin treated cancer cells increased macrophage expression of M1-related cytokines IL-12 and TNF-α and attenuated M2-related cytokines IL-8, IL-10, and TGF-β expression. Furthermore, metformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 34 publications
1
106
1
Order By: Relevance
“…The current study provides evidence that MOs cultured with breast cancer cells exhibited high levels of iNOS, but remain without marked change when treated with MET. Our observations are in agreement with earlier findings demonstrating that MET induces antitumoral activity of macrophages during breast cancer (49) and suppresses polarization toward pro-tumoral phenotypes (50). Although arginase activity was downregulated in untreated co-cultured cells, it was upregulated after MET treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The current study provides evidence that MOs cultured with breast cancer cells exhibited high levels of iNOS, but remain without marked change when treated with MET. Our observations are in agreement with earlier findings demonstrating that MET induces antitumoral activity of macrophages during breast cancer (49) and suppresses polarization toward pro-tumoral phenotypes (50). Although arginase activity was downregulated in untreated co-cultured cells, it was upregulated after MET treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Chiang et al, demonstrated the ability of this drug to inhibit the change of the TAMs phenotype to anti-inflammatory. This was done by the effect of metformin on the increase in AMPK activity and the regulation of the AMPK-NF-κB axis [139]. Similar conclusions were made by Wang et al, who additionally emphasized the anti-angiogenic effects of the drug by inhibiting VEGF expression [141].…”
Section: Metformin and Immune Microenvironment Of Gliomamentioning
confidence: 68%
“…In the case of malignant tumors such as GBM, TAMs adopt anti-inflammatory phenotype resulting in the production of anti-tumor immune response inhibiting cytokines, promoting tumor growth and angiogenesis [135][136][137][138]. This is associated with an unfavorable prognosis, which has been demonstrated, among others, in the case of glioma as well as prostate, bladder, breast, and lung cancers [139,140]. Recently, some researchers have suggested the potential effect of metformin in regulating polarization of TAMs reflecting their phenotype.…”
Section: Metformin and Immune Microenvironment Of Gliomamentioning
confidence: 99%
“…Various conditions can stimulate AMPK in the body, such as calorie restriction, which depresses cellular energy supplies and triggers AMPK. This is the reason that calorie constraint has been detected to diminish malignancy occurrence and augment cancer cell death in animal models (15)(16)(17)(18).…”
Section: Methodsmentioning
confidence: 99%